EFEKTIVITAS MEDIA PEMBELAJARAN PEDULI LINGKUNGAN PERBANTUAN SMART APP CREATOR (SAC) DALAM PENINGKATAN PENGETAHUAN REMAJA DI KELURAHAN SEKARAN - Supriyati; Dewi Liesnoor Setyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Environmental problems in Indonesia are increasingly concerning, so there is a need for breakthroughs to increase environmental awareness from an early age. The level of environmental knowledge and awareness among adolescents in Sekaran Sub-District is still low. As the next generation, adolescents need to be equipped with environmental knowledge to increase their concern for the environment.This study aims to develop, implement, and analyze the effectiveness of the Environmental Care media assisted by Smart App Creator (SAC) in improving adolescents' environmental knowledge in Sekaran Sub-District.The research method used a quantitative approach with a pre-experimental design, one group pretest-posttest. The research subjects were adolescents aged 11-15 years in RW 4, Sekaran Village, selected using purposive sampling. Data were collected through observation, tests, and questionnaires. Data analysis techniques included descriptive analysis, N-Gain test, Shapiro-Wilk normality test, Wilcoxon Signed Rank Test, and response analysis using a 4-point Likert scale.The results showed that the media had a feasibility level of 85.2% in the very feasible category. The aspect of response to the media obtained a score of 91.10% in the very good category. There was an increase in the average pretest score from 67.5 to 85.5 in the posttest. The N-Gain test result was 0.480 in the medium category. The Wilcoxon test result showed an Asymp. Sig. value of 0.001 < 0.05, indicating a significant difference between the pretest and posttest results. It is concluded that the Environmental Care learning media based on SAC is effective in improving adolescents environmental knowledge in Sekaran Sub-District